An experimental model for sonar sensors - Fonseca, Jaime C. (2001)
This paper describes an empirical model of the time-of-flight of a sonar sensor, derived from data collected with a Polaroid ultrasonic range finder. The goal of this model is to enable the acquisition of the profile of surfaces with a minimum error. These surfaces can present regions with different depths, corners and specular surfaces. To minimize the constraints of sonar sensors some software and hardware options are described and an empirical model obtained from real time data is presented. This model is based in two proposed concepts: Points of Constant Depth (PCD) and Areas of Constant Depth (ACD).